2012
DOI: 10.1103/physrevb.85.125431
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly confined surface plasmon modes with doped graphene sheets in the midinfrared and terahertz frequencies

Abstract: We investigate through analytic calculations the surface plasmon dispersion relation for monolayer graphene sheets and a separated parallel pair of graphene monolayers. An approximate form for the dispersion relation for the monolayer case was derived, which was shown to be highly accurate and offers intuition to the properties of the supported plasmon mode. For parallel graphene pairs separated by small gaps, the dispersion relation of the surface plasmon splits into two branches, one with a symmetric and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(152 citation statements)
references
References 51 publications
0
148
0
4
Order By: Relevance
“…The choice of graphene for the implementation of this miniaturized antenna is twofold. First, graphene shows excellent conditions for the propagation of SPP waves at frequencies in the terahertz band 23,24 , that is, much lower frequencies than the SPP waves observed in noble metals, typically in the optical domain 25 . Second, graphene allows to dynamically tune the antenna properties by means of an electrostatic bias 29 .…”
Section: Antenna Modelmentioning
confidence: 99%
“…The choice of graphene for the implementation of this miniaturized antenna is twofold. First, graphene shows excellent conditions for the propagation of SPP waves at frequencies in the terahertz band 23,24 , that is, much lower frequencies than the SPP waves observed in noble metals, typically in the optical domain 25 . Second, graphene allows to dynamically tune the antenna properties by means of an electrostatic bias 29 .…”
Section: Antenna Modelmentioning
confidence: 99%
“…Moreover, the interband conductivity (due to the electron transition) is given by [12]: (2) It is worth noting that Equation 1 and Equation 2 are valid for μ g >> k B T and T = 300 K (room temperature), thus, k B T ≈ 26 meV.…”
Section: Graphene-based Waveguides Featuresmentioning
confidence: 99%
“…Both theoretically and experimentally, it has been shown that graphene plasmons can couple with surface phonons of polar substrates [3,12], and with plasmon modes of metal particles or a metal surface [7,10,15]. Coupled plasmon modes resulted from the coupling of two graphene layers have also been studied [16][17][18][19]47]. Coupled plasmon modes of these systems can be determined from the following equation when the retardation effect is ignored [15]: (15) where is the thickness of the substrate that has the permittivity , is the thickness of the spacer between the graphene layer and the substrate, , and , , are respectively the permittivity of the medium below the substrate, the permittivity of the spacer, and the permittivity of free space above the graphene layer, as shown in Figure 3b,c.…”
Section: Plasmon Dispersionmentioning
confidence: 99%
“…Note that does not have to be equal to of the upper graphene layer because they do not necessarily have the same or . For simplicity, here we set ; then with given by Equation (18), Equation (15) becomes (19) which has been derived previously [47]. Equation (19) can also be derived by finding zeros of the linear-response function of the double layer graphene system [15].…”
Section: Double-layer Graphenementioning
confidence: 99%